(untitled) (The Peerian Journal, 2024)
The article presents the pilot device of the polymer composite coating equipment for tarpaulin seams. As a result of experimental studies, equipment and a 2-meter diameter rotary table are presented, which ensure the maximum breaking force of tarpaulin seams when they are made with silicone polymer coating.